Bridging the gap between DeafBlind minds: interactional and social foundations of intention attribution in the Seattle DeafBlind community - Edwards, Terra (Frontiers in Psychology, 2015)
This article is concerned with social and interactional processes that simplify pragmatic acts of intention attribution. The empirical focus is a series of interactions among DeafBlind people in Seattle, Washington, where pointing signs are used to individuate objects of reference in the im-mediate environment. Most members of this community are born deaf and slowly become blind. They come to Seattle using Visual American Sign Language, which has emerged and developed in a field organized around visual modes of access. However, as vision deteriorates, links be-tween deictic signs and the present, remembered, or imagined environment erode in idiosyncratic ways across the community of language-users, and it becomes increasingly difficult for partici-pants to converge on objects of reference. In the past, DeafBlind people have addressed this problem by relying on sighted interpreters. Under the influence of the recent “pro-tactile” movement, they have turned instead to one another to find new solutions to their referential prob-lems. Drawing on analyses of 120 hours of videorecorded interaction and language-use, detailed fieldnotes collected during twelve months of sustained anthropological fieldwork, and more than 15 years of involvement in this community in a range of capacities, I show how DeafBlind peo-ple are generating new and reciprocal modes of access to their environment, and how this pro-cess is aligning language with context in novel ways. I propose two mechanisms that can account for this process: deictic integration and embedding in the social field. I argue that together, these interactional and social mechanisms yield a deictic system set to retrieve a restricted range of values from the extra-linguistic context, thereby attenuating the cognitive demands of intention-attribution and narrowing the gap between DeafBlind minds.